Jernang Etnobotani Jernang Masyarakat Pedalaman Bireun - Muhammad Ridhwan; Nurlena Andalia; Armi Armi; Yuhasriati Yuhasriati (Universitas Islam Negeri Mataram, 2018)
Jernang is one of the wild trees that are from the family of rattan with the genus of Daemonorops. The objective of this research is to know the availability, user, harvest, and conservation of the Jernang as well as the barrier faced by the jernang hunters, jernang harvest, and jernang conservation. This study is the done using descriptive research methodology. Respondents were chosen by purposive sampling. They were chosen with special considerations such as they must be the jernang hunters or the people who well understand the jernang. The data were collected through interview and participant observation and then analyzed descriptively. The research findings showed that the respondents still hunted the jernang in the forest and they sold to the buyers in their villages. Jernang fruits were processed by extracting them to get their substances. The conservation efforts have many threats due to the expansion of the palm plantation. The lack of people knowledge of good jernang for the seed is also one of the barriers of conservation.